Pelatihan Bertanam Hidroponik dan Organik Untuk Pertanian Masa Depan Kepada Santri dan Siswa SMK Pondok Pesantren Shofa Marwa Arjasa Jember - Endang Sri Wahyuni; Ari Septianingtyas Purwandhini (Al-Khidmah Jurnal Pengabdian Masyarakat, 2022)
The use of the yard is still not done well. One way to use the yard is with hydroponics. Moreover, hydroponics does not require large costs. Hydroponic materials can be made by utilizing used goods. Hydroponics is very suitable for students and students of the Shofa Marwa Islamic Boarding School in Jember Regency who can take advantage of the yard around the Islamic boarding school. The method used in this training is Student Central Learning (SCL), with a combination of lectures, discussions and hands-on practice. The results of this service activity were successful as shown by the ability of participants to make hydroponic and organic plants using locally available materials. The follow-up to the results of this activity is to carry out hydroponic planting by the Santri and Students of the Shofa Marwa Islamic Boarding School. In addition, the installation of Nutrient Film Technique (NFT), mini shelves of the Deep Flow Technique (DFT) system and aquaponics for hydroponic vegetable cultivation for 518 plants was also made. At the same time planting pre-organic onions in polybags.